Plasma Serotonin Levels and Depression Scores in Informal Caregivers of Patients with Dementia and without Dementia: A Systematic Review - Widyadharma, I Putu Eka; Budaya, I Made Maha Candra; Widyastuti, Ketut (Indonesian Journal of Medicine, 2026)
Background: Depression frequently affects informal caregivers, particularly those caring for dementia patients due to greater emotional and caregiving burdens. This study aims to compare depression levels and plasma serotonin concentrations between dementia and non-dementia caregivers. Subjects and Method: A systematic review was conducted using PRISMA guidelines. Articles were searched from PubMed, ScienceDirect, and Google Scholar between 2015–2024 using the keywords: dementia caregiver, non-dementia caregiver, depression, and serotonin. Nine primary observational studies met the inclusion criteria: full-text availability, adult informal caregivers, and quantitative measurement of depression and/or serotonin. Data were synthesized narratively. Results: Most studies demonstrated higher depression levels among dementia caregivers compared to non-dementia caregivers. Emotional distress, patient behavioral symptoms, and caregiving duration were identified as major contributing factors. One study showed lower plasma serotonin associated with higher depressive scores, supporting possible biological involvement. Conclusion: Dementia caregivers exhibit greater depressive symptoms than non-dementia caregivers, potentially linked to caregiving burden and serotonin imbalance. Early psychological screening and targeted support interventions are recommended.